Electronic commerce and the revolution in financial markets - Ming Fan... (South-Western/Thomson Learning, 2002)
This comprehensive book clearly and concisely outlines how Internet technology impacts financial markets. It includes a re-examination of how financial markets, such as the Nasdaq or the NYSE "work," which parties are involved, how the price is produced, how transactions are settled, and more. Written by authors intimately involved in researching and shaping the ongoing transformation in financial markets, this text provides students the chance to look at the day-to-day operations and developments of the marketplace